EFFECTIVENESS ANALYSIS OF THE GRAMEEN BANK SYSTEM TO ADRESS TROUBLED CREDIT COOPERATIVE PARTNER DHUAFA IN JAKARTA - Dian Parawansa; Jusni; umi iriana fabanjo (Scientia Integritas Utama, 2023)
This study aims to (1) analyze the effect of human capital (X1), social capital (X2) and SOP (X3) on the effectiveness of the Grameen Bank system in the control of non-performing loans and (2) dominant variables affecting the effectiveness of Grameen Bank in a credit control system is problematic in the Komida Center office. This research was conducted at the Central Office Cooperative Partner Dhuafa Jakarta for 2 months, from April to May 2012. The study design used is descriptive and associative. The population in this study were employees of Koperasi Mitra Dhuafa Headquarters Jakarta as many as 36 people. In relation to the population is relatively small and accessible in their entirety by the researchers, the use of saturated samples. The data were analyzed by multiple linear regression. The results showed that (1) human capital (X1), social capital (X2) and SOP (X3) have a positive and significant impact on the effectiveness of the Grameen Bank system in the control of non-performing loans at the Komida Center and (2) human capital has the most dominant on the effectiveness of the Grameen Bank system in the control of non-performing loans at the Komida Center than both other variables.